Depth gradient in the resource use of a fish community from a semi‐enclosed sea. (11th May 2017) - Giraldo, Carolina; Ernande, Bruno; Cresson, Pierre; Kopp, Dorothée; Cachera, Marie; Travers‐Trolet, Morgane; Lefebvre, Sébastien
Abstract: Depth is one of the environmental variables influencing the structure of marine food webs by directly or indirectly influencing benthic‐pelagic coupling and predator‐prey relationships. In shallow waters, the high degree of connectivity between pelagic and benthic networks results in complex systems with multiple interactions. Digestive tract (DT) and stable isotope (SI) analyses were used to investigate depth‐related changes in feeding patterns for 33 fish species (eastern English Channel [EEC]) collected between 5 m and 80 m depth. Fish species were first arranged into functional groups based upon trophic and habitat similarities. DTs were used to determine the general topology of the food web and SIs were used to estimate the contributions of different sources to fish diets. At the scale of the aggregated EEC food web, the main food sources for all groups were of benthic origin (> 50%). The aggregated food web was then used as a template to explore the influence of depth on resource use by predatory fish. Mixing models including depth as a continuous covariate successfully untangled and identified different feeding strategies among functional groups. In shallow waters, fish species benefited from both pelagic and benthic prey whereas, in deeper waters, they fed predominantly on either benthic or pelagic sources depending on their habitat preferences. Our results support the hypothesis of a stronger benthic‐pelagic coupling in shallow waters, notably through fish diet, and highlight the importance of including environmental factors such as depth as proxies of habitat variation to fully understand resource use and food web structure in epicontinental seas.